2018
DOI: 10.4047/jap.2018.10.6.408
|View full text |Cite
|
Sign up to set email alerts
|

Effect of non-thermal plasma on the shear bond strength of resin cements to Polyetherketoneketone (PEKK)

Abstract: PURPOSEThis study aimed to assess the effect of non-thermal plasma on the shear bond strength of resin cements to polyetherketoneketone (PEKK) in comparison to other surface treatment methods.MATERIALS AND METHODSEighty PEKK discs were subjected to different surface treatments: (1) Untreated (UT); (2) Non-thermal plasma (NTP); (3) Sandblasting with 50 µm Al2O3 particles (SB); and (4) Sandblasting + Non-thermal plasma (SB+NTP). After each surface treatment, the contact angle was measured. Surface conditioning w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…These results are consistent with previous reports of a significant decrease in SBS due to thermocycling after NTP treatment [23,25,38]. Therefore, the SBS after NTP treatment may be affected by thermal stress, the compositions of resin cement, and low resistance to hydrolysis of the van der Waals bond [39,40]. Despite these findings, we suggest that NTP treatment probably helps to increase the initial SBS between Y-TZP and self-adhesive resin cement.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with previous reports of a significant decrease in SBS due to thermocycling after NTP treatment [23,25,38]. Therefore, the SBS after NTP treatment may be affected by thermal stress, the compositions of resin cement, and low resistance to hydrolysis of the van der Waals bond [39,40]. Despite these findings, we suggest that NTP treatment probably helps to increase the initial SBS between Y-TZP and self-adhesive resin cement.…”
Section: Discussionsupporting
confidence: 92%
“…Unlike other adhesives, 10-methacryloyloxydecyl dihydrogen phosphate and self-etching universal adhesive containing silane (Single Bond Universal) presented efficient shear bond strength in all treatments. Similarly, the non-thermal plasma surface modification with sandblasting increased the shear bond strength between the resin cement and PEKK [50] . Universal adhesive shows similar bonding as visio-link (light-polymerizing PMMA and composite resin primer) for PEKK [47] .…”
Section: Properties Of Pekkmentioning
confidence: 90%
“…These findings correspond to previous studies where the bond strength of NTP-treated zirconia decreased significantly after thermocycling [ 32 , 34 , 48 ]. Thus, the RS may be associated with a low resistance to thermal stress and hydrolysis of chemical bonds following NTP processing [ 49 , 50 ]. In particular, previous studies have reported that, when resin cement comes in contact with oxygen, oxygen reacts with radical polymerization catalysts to stimulate resin monomer molecules and prevent them from binding to each other [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%